EVALUATION OF ANTIBACTERIAL ACTIVITY OF ENDOPHYTIC FUNGI ASPERGILLUS JAPONICUS ISOLATED FROM TRIDAX PROCUMBENS L. - Aharwal, Ravindra Prasad; Kumar, Suneel; Thakur, Yogita; Deshmukh, Loknath; Sandhu, Sardul Singh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main purpose of the present study was to isolate the endophytic fungi from Tridax procumbens L. and evaluate their antibacterial activity at different concentration of compatible solvents extracted metabolites against the test pathogenic bacterial strain, as well as the molecular characterization of potent endophytic fungal isolate that showed the maximum antibacterial activity. Methods: The endophytic fungi were isolated from the different parts of the collected T. procumbens plant. Screening of endophytic fungi for the antibacterial activity was scrutinized against five pathogenic bacteria such as Bacillus subtilis, Streptococcus pyogenes, Escherichia coli, Klebsiella pneumoniae, and Salmonella typhimurium using agar well diffusion method. After screening, the metabolite of the potent fungal isolate was extracted using different solvents by solvent-solvent extraction procedure and observed their antibacterial activity. For molecular identification of the fungi, the DNA was extracted, quantified, and amplified using two oligonucleotide primers ITS4 and ITS6 in polymerase chain reaction. Results: In the present study, five endophytic fungi were isolated from medicinal plant T. procumbens and screened for their antibacterial activity against E. coli (22.60±0.32 mm), S. typhimurium (19.26±0.23 mm), S. pyogenes (16.36±0.18 mm), K. pneumoniae (14.26±0.54 mm), and B. subtilis (14.43±0.27 mm) bacterial strain. The endophytic fungal strain A. japonicus isolated from T. procumbens was showed the significant antibacterial activity against the pathogenic bacteria. The morphological identification of all the isolated endophytic fungi was observed on the basis of their macroscopic and microscopic characteristics, and the molecular identification of the potent fungal strain was observed through 18s rRNA sequence analysis. Using solvent-solvent extraction technique, different solvent residues of the potent fungal metabolite were extracted in benzene, n-,butanol and toluene. The n-butanol solvent extract exhibited a maximum zone of inhibition against the test bacterial strains. Conclusion: The present study reveals that the endophytic fungi serve as a potential source for the production of effective bioactive compounds.